Enhanced visible-light-driven photocatalytic potential of magnetic NiMnFeO4/g-C3N4 nanocomposites for degradation of aqueous organic pollutants: Schiff-base ligand-assisted sol–gel auto-combustion synthesis, characterization and mechanism analysis - Samira Mazaheri; Rozita Monsef; Forat H. Alsultany; Masoud Salavati-Niasari (Applied Water Science)
Abstract Globally, the contamination of aquatic systems and wastewater by dyes is highlighted as a critical concern for human beings. Therefore, it is necessary to construct novel heterostructure photocatalysts with broadened light absorption range and enhanced charge transfer rates. The primary objective of this research is to achieve the NiMnFeO4 phases through an auto-combustion route with exploring various Schiff base ligand’s effects such as H2Salen, H2Salpn, and H2Salophen on crystalline structural and morphological features. Following this, a composite of NiMnFeO4 nanoparticles and graphitic carbon nitride (g-C3N4) nanosheets was synthesized via a sonochemical-assisted co-precipitation process, in which diverse weight proportions of nano-NiMnFeO4 was employed. To unveil the crystalline structure, chemical composition, morphology and magnetic properties of NiMnFeO4/g-C3N4 nanocomposites, multiple spectroscopic and microscopic techniques were carried out. The outcomes displayed that pure NiMnFeO4 phase synthesized in the presence of H2Salpn have optical bandgap energy of 2.0 eV and morphologically desirable nano-sample. The photocatalytic efficiencies and kinetic investigation of as-obtained NiMnFeO4, g-C3N4 and various NiMnFeO4/g-C3N4 nanocomposite’s types were perused through degradation of cationic malachite green and anionic eosin dyes under visible light irradiation. The content of nano-NiMnFeO4 in binary component systems changed the yields of the photocatalytic process and NiMnFeO4/g-C3N4 (0.25:1) nanocomposites revealed highest eosin degradation proficiency (95.12%) in visible region after 120 min. Furthermore, the proposed mechanism underlying eosin degradation via photocatalytic activity was thoroughly investigated via reactive species scavenging experiments. In photoreactions conducted by optimum NiMnFeO4/g-C3N4 (0.25:1) sample, both hydroxyl and superoxide radicals performed the superior role for the photocatalytic breakdown of eosin below visible lamp.